A prospective-longitudinal study on the association of anxiety disorders prior to pregnancy and pregnancy- and child-related fears. (May 2016) - Martini, Julia; Asselmann, Eva; Einsle, Franziska; Strehle, Jens; Wittchen, Hans-Ulrich
Highlights: Pregnancy- and child-related fears were prospectively investigated. Pregnancy- and child-related fears were generally common. Multiple anxiety disorders predicted pregnancy- and child-related fears. Comorbid anxiety disorders predicted pregnancy- and child-related fears. Results were stable when considering potential confounders (e.g. prior abortion). Abstract: This study aimed to investigate the relation between anxiety disorders prior to pregnancy and specific pregnancy- and child-related fears during pregnancy and after delivery. 306 expectant mothers were interviewed regarding anxiety (and depressive) disorders prior to pregnancy and pregnancy- and child-related fears (e.g. fear of labor pain, fear of infant injury) using the Composite International Diagnostic Interview for Women (CIDI-V). Pregnancy- and child-related fears were particularly pronounced in women with multiple anxiety disorders and women with comorbid anxiety and depressive disorders prior to pregnancy. Further analyses revealed associations between particular anxiety disorders and specific pregnancy- and child-related fears. Results remained stable when considering potential confounders such as maternal age, education, marital status, parity, prior abortion and preterm delivery or low birth weight. Our study suggests that especially women with multiple anxiety and/or comorbid depressive disorders may benefit from early targeted interventions to prevent an escalation of anxiety and fears over the peripartum period.